Collagen: Structure and Mechanics - Fratzl, Peter (Springer, 2017)
Collagen type I is the most abundant protein in mammals. It confers mechanical stability, strength and toughness to a range of tissues from tendons and ligaments, to skin, cornea, bone and dentin. These tissues have quite different mechanical requirements, some need to be elastic or to store mechanical energy and others need to be stiff and tough. This shows the versatility of collagen as a building material. While in some cases (bone and dentin) the stiffness is increased by the inclusion of mineral, the mechanical properties are, in general, adapted by a modification of the hierarchical structure rather than by a different chemical composition. The basic building block of collagen-rich tissues is the collagen fibril, a fiber with 50 to a few hundred nanometer thickness. These fibrils are then assembled to a variety of more complex structures with very different mechanical properties. As a general introduction to the book, the hierarchical structure and the mechanical properties of some collagen-rich tissues are briefly discussed. In addition, this chapter gives elementary definitions of some basic mechanical quantities needed throughout the book, such as stress, strain, stiffness, strength and toughness.